Lessons from badly behaved technology transfer to a professional context. (7th December 2004) - Chambers, David W.
Technology development and transfer to professional practices is explored using the example of dentistry. Oral health in the USA has improved dramatically in the past forty years, but paradoxically, this has been the result of an inexpensive technology, systemic fluoridation, that is outside dental practice. Also paradoxically, the improvement in oral health has been accompanied by increasing demand for dental care and an even greater profit to dentists. Dentists have maintained control over all aspects of technology. This includes technology development, channels for diffusing information regarding innovations and of evaluating their potential value, and adoption and financing decisions. Most innovation is incremental and involves changes of materials and supplies, with capital investments costing over a few thousand dollars being unusual. The criteria used by dentists to evaluate technology are personal and pragmatic. Because they are the principal users of technology, it must "feel right in a dentist's hands". Dentists also seek protection from the environment they cannot control by establishing management mechanisms that are largely outside their practices. It is suggested that technology in dentistry is "pulled" based on professional self-image in a teleological fashion rather than "pushed" in a logical fashion based on the objective characteristics of technology and its potential impact on customers or the environment.